The Acquisition Algorithm for Clustered Subgroup Based on Sensor Balance - Zhang JIANPEI (Sensors & Transducers, 2013)
One of the main tasks of social aware computing research is crowd behavior and interaction analysis, it is important to understand the formation of community relationship structure. This paper based on perceived balance, proposes the balanced clustered subgroup with its individual coefficients in the environment for group behavior analysis. For transforming iterative optimization in computing process, it also puts forward balance clustering threshold and CIT algorithm for the division of subgroups, and CIOE algorithm for clustering coefficient acquisition. The experimental results show that the algorithm uses the parameters from the integration of time context and social situation on the basis of division in balance clustering subgroup, to acquire individual balance perception values and analyze the aggregation intensity in a group and individual behaviors.